2017
DOI: 10.1002/pc.24560
|View full text |Cite
|
Sign up to set email alerts
|

Composite manhole covers prepared with recycled printed circuit boards as a reinforcing filler

Abstract: Waste circuit boards particles (CBPs) were utilized as a reinforcing filler to prepare bulk molding composites (BMCs) for the manufacture of composite manhole covers (CMCs) without reinforcing ribs. The effects of CBPs and conventional CaCO 3 on the mechanical properties of the BMCs were comparatively determined. Compared to CaCO 3 , CBPs showed a higher compatibility with unsaturated polyester resin (UPR) while effectively improving the fluidity of premix and the mechanical properties of the BMC. To enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…New reticular membranes or organic long chains on the surface of the modified particles were formed from the associated reaction of hydrolyzed KH-550. A reticular membrane led to an organic surface of the N-WPCBs and decreased the polarity of the N-WPCBs, which enhanced the compatibility of the PP matrix and N-WPCB particles [ 10 ]. Interfacial bonding between the PP matrix and N-WPCB particles was enhanced through the organic long chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New reticular membranes or organic long chains on the surface of the modified particles were formed from the associated reaction of hydrolyzed KH-550. A reticular membrane led to an organic surface of the N-WPCBs and decreased the polarity of the N-WPCBs, which enhanced the compatibility of the PP matrix and N-WPCB particles [ 10 ]. Interfacial bonding between the PP matrix and N-WPCB particles was enhanced through the organic long chains.…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al reported that N-WPCBs were used as reinforcing fillers in rubbers. The tensile strength of rubber composites sharply increases to 18 MPa with the use of grafted polymers, which also significantly improves the thermal oxidation resistance [ 10 ]. Grigorescu et al used N-WPCBs as fillers to improve the fire resistance of thermoplastic composites based on recycled polypropylene and diene block copolymers, and the impact strength was observed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, research on manholes and the paving around manholes mostly focuses on manhole settlement mechanisms [6], new manhole structures [7][8][9], damage analysis of the paving around manholes [10], and treatment technology for pavement damage [11,12], and the control of damage to paving around manholes has improved to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Printed circuit boards as fundamental building blocks for electronic device have been increasingly applied in all sorts of areas of electronic industry . With the continuous renewal of electronic products, the resulting waste printed circuit boards (WPCB) including off‐cuts during manufacturing and end‐of‐life components are extensively stacking up, the proper deposal of WPCB therefore has been the issue of common concern from scientific and industrial researchers .…”
Section: Introductionmentioning
confidence: 99%